EFFECT OF COMBINING LEUCAENA AND INDIGOFERA LEAVES IN SWAMP GRASS-BASED DIETS ON DIGESTIBILITY, RUMEN FERMENTABILITY AND METHANOGENESIS - Riswandi,; A. I. M. Ali,; Muhakka, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This research was conducted to evaluate the effect of the combination of Leucaena and Indigofera in swamp grass-based rations on the quality or quantity of feed produced. The research was carried out based on a completely randomized design (CRD) consisting of four treatments and four replications. The types of forage used include termite Bento grass (Leersia hexandra) from swamp land; legumes Leucaena and Indigofera. The treatments consisted of A = swamp grass and concentrate (70%:30%), B = swamp grass, Leucaena and concentrate (40%:30%:30%), C = swamp grass, Indigofera and concentrate (40%:30%:30%), D = swamp grass, Leucaena, Indigofera and concentrate (40%:15%:15%:30%). The observed variables consisted of dry matter digestibility (DMD), pH, total Volatile Fatty Acid (TVFA), N-ammonia (N-NH3), partial VFA, methane gas, total bacteria and protozoa. The study showed that the combination of tree legumes increased (P